139k views
2 votes
Given f(x) = 2x2 - 3, what is the value of f(x + 3)?

A- 2x2 + 12x + 15
B.- 2x2 + 15
C.- 2x2 + 12x + 9
D.- 2x2 + 12x - 15

User Prasob
by
6.5k points

1 Answer

4 votes

Answer:

Answer A is correct.

Explanation:

Please note the difference beteen f(x+3) and f(3).

So f(x + 3) means, where you see x in the equation, you substitute x+3. (This is a recursive entry).

f(x)= 2x² - 3

f(x)= -3 + 2x²

f(x)= -3 + 2* (x+3)²

f(x)= -3 + 2* (x+3) * (x+3)

f(x)= -3 + 2* (x² + 3x + 3x + 9)

f(x)= -3 + 2* (x² + 6x + 9)

f(x)= -3 + 2x² + 12x + 18

f(x)= 2x² + 12x + 18 -3

f(x)= 2x² + 12x + 15

So answer A is the correct answer

User Vitaly Babiy
by
5.9k points